Real-time polymerase chain reaction detection of Lichtheimia species in bandages associated with cutaneous mucormycosis in burn patients. Issue 1 (May 2018) - Fréalle, E.; Rocchi, S.; Bacus, M.; Bachelet, H.; Pasquesoone, L.; Tavernier, B.; Mathieu, D.; Millon, L.; Jeanne, M.
Summary: Background: Cutaneous mucormycoses, mainly due to Lichtheimia ( Absidia ), have occurred on several occasions in the Burn Unit of the University Hospital of Lille, France. Aim: To investigate the potential vector role of non-sterile bandages used to hold in place sterile gauze used for wound dressing. Methods: Mycological analysis by conventional culture, Mucorales real-time polymerase chain reaction (qPCR), and Lichtheimia species-specific qPCR were performed on eight crepe and six elasticized bandages that were sampled on two independent occasions in March 2014 and July 2016. Characteristics of the seven Lichtheimia mucormycoses which occurred in burn patients between November 2013 and July 2016 were also collected to assess the epidemiological relationship between potentially contaminated bandages and clinical infections. Findings: One Lichtheimia corymbifera strain was isolated from a crepe bandage by culture, and Lichtheimia spp. qPCR was positive in six out of eight crepe and four out of six elasticized bandages. Using species-specific qPCR, Lichtheimia ramosa, Lichtheimia ornata, and L. corymbifera were identified in six out of ten, five out of ten, and four out of ten bandages, respectively. In patients with mucormycosis, L. ramosa and L. ornata were present in five and two cases, respectively. Conclusion: Our data support the utility of Mucorales qPCR for epidemiological investigations, the potential role of these bandages in cutaneous mucormycoses in burn patients in our centre, and, consequently, the need for sterile bandages for the dressing of extensive wounds.